Management and Immediate Outcome of Common Pediatric Oncological Emergencies: A Single-Center Prospective Study - Raman, Radhika; Ramakrishna, Sreenidhi; Muthukrishnan, Lakshmi (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: The initial presentation of childhood malignancies is often an emergency. Timely recognition and effective management of pediatric oncological emergencies are crucial for improving patient outcomes. This prospective study aimed to investigate the nature of oncological emergencies, emergency management strategies, and immediate outcomes in children presenting with these events. Material and Methods: This prospective study was conducted on 83 children with 110 visits, with a median age of 6 years. Data collected included the nature of the oncological emergency, emergency management, and immediate outcomes. Results: Leukemia was the most common malignancy, accounting for 50.6% of cases, with 92.8% being acute lymphocytic leukemia. Intracranial malignancies constituted 26.5%, with 59% of these being posterior fossa tumors. The most frequent presenting symptoms included fever (36.4%), severe anemia (18%), febrile neutropenia (16.45%), tumor lysis syndrome (TLS) (8%), and respiratory distress (4.5%). Neurological symptoms were present in 31% of patients. Emergency management included parenteral antibiotics in 42.7% of cases, packed cell transfusions in 16.4%, and intensive care admission in 26.5%. Twelve patients required neurosurgical procedures. Blood cultures were negative in 90.4% of cases. Conclusion: This study highlights the diverse nature of pediatric oncological emergencies. Effective management often involves a multidisciplinary approach, including supportive care, antibiotics, transfusions, and intensive care. While blood cultures are often negative, early identification and appropriate treatment are essential for improving immediate outcomes in children with oncological emergencies.